Programmed Death Ligand 1 Expression in Laryngeal Squamous Cell Carcinomas and Prognosis - Sebnem Batur; Zeynep Ecem Kain; Emine Deniz Gozen; Nuray Kepil; Ovgu Aydin; Nil Comunoglu (SAGE Publishing, 2020)
Aim: We aimed to show the immunohistochemical expression of programmed death ligand 1 (PD-L1) in laryngeal squamous cell carcinomas (SCCs). Materials and methods: The study includes 52 laryngeal SCC cases that underwent surgical resection. Immunohistochemical staining of PD-L1 (Clone 22C3) was applied to the sections obtained from paraffin blocks. Combined Positive Score (CPS) was evaluated as described in manuals. Tumor Proportion Score (TPS) was assessed by the percentage of positive tumor cells which were designated as positive if ⩾1% of the tumor cells showed membranous staining. Results: There were 35 cases (67.3%) having CPS < 1 and 17 cases (32.7%) having CPS ⩾ 1. There was no relationship between CPS, TPS, and the clinicopathological data. Conclusion: Further studies with a large number of advanced-stage cases are needed.